Adrienne Kennedy Reader - Kennedy, Adrienne (Book collections on Project MUSE., 2001)
Adrienne Kennedy has been a force in American theatre since the early 1960s, influencing generations of playwrights with her hauntingly fragmentary lyrical dramas. Exploring the violence racism visits upon people's lives, Kennedy's plays express poetic alienation, transcending the particulars of character and plot through ritualistic repetition and radical structural experimentation. The Adrienne Kennedy Reader is the first comprehensive collection of works by one of our greatest living playwrights.